INTERACTIVE METHODS IN TEACHING ENGLISH: DISTINCTIVE FEATURES - Khaldarchayeva Gaukhar Serikbayevna (European Science Publishing, 2026)
This article discusses the recognition of knowledge, its process, advantages, and planning, as well as language-teaching activities and games, and the challenges encountered in the application of interactive methods. It highlights that, in lessons conducted through interactive methods, students’ own life knowledge and experiences are taken into account. Instead of merely providing information, the teacher enriches the lesson by drawing on students’ existing knowledge and, rather than simply presenting information, encourages students to express independent opinions, thereby broadening their worldview.
Keywords: Planning, training, process, problems, interactive method, advantages, collaboration, composition, presentation, development.